Systemic Reflecting Team Training: Perceptions and Experiences of South African Educational Psychologists. Issue 2 (15th March 2019) - Amod, Zaytoon; Miller, Jodi
Abstract: There is limited research on the application of systemic family therapy in developing countries. This qualitative study explored the perceptions and experiences of 12 educational psychologists and a family therapy trainer, who have worked within a systemic reflecting team using Tom Andersen's method of training and supervision. The semi-structured interview findings suggested positive perceptions of systemic intervention, despite various challenges experienced in its implementation within the South African context. The educational psychologists identified their reflecting team experiences as being beneficial for both their professional development and current practices. Future research which investigates the reflecting team process in action is recommended.